(untitled) (Siddhajyoti Interdisciplinary Journal, 2026)
This thematic review explores the perceptions, impacts, and challenges of gamification in teaching and learning of English as a Foreign Language (EFL). It has synthesized the results of 20 peer-reviewed articles on gamification in various settings, with a focus on both students and teachers. Based on the results, the study participants find gamification in learning to be enjoyable, stimulating, and extremely motivating, which helps build confidence and foster teamwork. The teachers consider it a vital tool for improving the classroom environment and enhancing student engagement. Although the application of gamification has a significant influence on improving the learning process and the acquisition of vital life skills, several challenges are associated with the practice, including technical issues, design challenges, potential stress to students due to competition, and financial constraints for teachers. Nevertheless, the general evidence suggests that EFL learning can be more interactive, engaging, and exciting through gamification, leading to enjoyable learning experiences. This review offers insights into maximizing the benefits of a gamified learning environment for educators, curriculum designers, and researchers. The study highlights the necessity of further investigation into the long-term effects of gamification in the English language classroom.